Antifungal activity of methanol extract of Pluchea Lanceolata against some fungi. - PREM SHANKAR PANDEY; UDAY PRATAP SINGH (International Journal of Pharma and Bio Sciences, 2019)
Increased agricultural production is attributed to excessive use of synthetic chemicals during the last century. This has raised a number of ecological and human health problems as most of them are associated with several harmful effects. Drawbacks associated with synthetic fungicides have given way to think of the biodegradable plant products, especially from medicinal plants as their alternative. Plants contain a wide range of antifungal compounds and many of them have been implicated in the natural resistance of several plants against pathogens. The present finding was on the plant Pluchea lanceolata which is used in Indian system of medicine in various diseases. The plant was dried and extracted with methanol by cold percolation. The methanolic extract was assessed against spore germination of plant pathogenic fungi, Alternaria brassicae, A. melongenae, Curvularia lanata, C. pallescens, Colletotrichum sp., C. musae, Erysiphe pisi, Helminthosporium spiciferum, Ustilage cynodontis. Alternaria melongenae, Colletotrichum sp., Helminthosporium spiciferum and Ustilage cynodontis were the most sensitive as complete inhibition of germination was obsereved in all the concentrations (200, 400, 600, 800, 1000 ppm) of the extract. Similar effect on Curvularia lanata and C. pallescens were recorded of 400, 600, 800 and 1000 ppm, whereas Alternaria brassicae did not germinate at 600, 800 and 1000 ppm. However, only 1000 ppm was effective against spore germination of Colletotichum musae and Erysiphe pisi. The findings thus suggest the possibility of its use for the control of plant diseases under field conditions.